Peningkatan Keterampilan Menulis Naskah Drama melalui Pendekatan Pembelajaran Kontekstual Siswa Kelas VIII RSBI-1 SMP N 12 Padang - Yurnelis . (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2012)
The background of this research is the low ability of the students in writing the role play text, in which they can not pass the minimum mastery criterion (KKM). The type of the research is Classroom Action Research which is employed in two (2) cycles. The act of the teaching and learning process is done by using CTL approach. Each cycle is done by integrating some CTL components and observed by the observers. The steps of the research are planning, doing, observation and reflection. The data are qualitative and quantitative. Qualitative data are collected from the observation and filed note while the quantitative data are collected from the result of students performance test. The research resuts shows that there is an increasing of student’s activity during teaching and learning processes after finishing the first and the second cycles. Furthermore, there is an increasing of students achievement result in writing the role play text from 68,38 in pre-cycle, which indicates that  40% of the students passed the KKM. Furthermore, the students achievement increases into 73,75 on the first cycle in which 64 % of students passed the KKM. Moreover, the second cycle shows that the average students’ grade is 88,25. This  grade means that 100% of the students pass the minimum mastery criteria (KKM). Keywords: writing, role play text, contextual teaching approach